MANFAAT PENGUATAN OTOT TRANSVERSUS ABDOMINIS DAN ROLLING RUG MASSAGE TERHADAP PERCEPATAN PENGELUARAN LOCHEA PADA IBU NIFAS - Cita Arunika Dewi; Wiwit Desi Intarti (Jurnal Inovasi Daerah, 2022)
Complications during pregnancy until delivery have an impact during the puerperium such as bleeding, uterine subinvolution, infection, and other complications. Adequate uterine contractions then the involution process is good and vice versa so that subinvolution occurs. During the puerperium there is a process of releasing lochea, the process of releasing lochea. The aim of the study was to determine the benefits of strengthening the transversus abdominis muscle and rollin rug massage on the acceleration of lochea expenditure in postpartum women. The research design used is a qualitative research with a case study research strategy. A sample of 3 respondents, research data was taken by using observation techniques, in-depth interviews and direct observation. After tabulating the existing data were analyzed using domain analysis. The results of this study indicate the acceleration of lochea expenditure by strengthening the transversus abdominis muscle and rolling rug massage. So it can be concluded that there are benefits of strengthening the transversus abdominis muscle and rollin rug massage to accelerate the release of lochea in postpartum women